Cardiac autoantibodies in dilated cardiomyopathy become undetectable with disease progression. Issue 1 (January 1997) - Caforio, A. L.; Goldman, J. H.; Baig, M. K.; Haven, A. J.; Dalla Libera, L.; Keeling, P. J.; McKenna, W. J.
Abstract : OBJECTIVE: To determine the relation of cardiac autoantibody and disease status in a consecutive series of patients with dilated cardiomyopathy by prospective antibody testing at diagnosis and at follow up. METHODS: Antibody status was assessed by indirect immunofluorescence in 110 patients with dilated cardiomyopathy (85 male, mean (SD) age 44 (13) years) at diagnosis and at follow up (mean (SD) 14 (12) months); in 57 of them cardiac specific anti-alpha myosin antibody titres were also measured by an enzyme-linked immunosorbent assay (ELISA). Patients underwent complete evaluation at diagnosis and clinical and non-invasive assessment at follow up, including exercise testing with maximal oxygen consumption measurements. RESULTS: The frequency of cardiac specific antibodies by immunofluorescence was lower at follow up than at diagnosis (28 (25%) v 11 (10%), P = 0.002). Mean (SEM) anti-alpha myosin antibody titres at follow up were also lower than at diagnosis (0.24 (0.02) v 0.30 (0.02), P = 0.038); 24% of patients at diagnosis and 14% at follow up had an abnormal ELISA result. None of the patients who were negative by immunofluorescence or ELISA at diagnosis became positive at follow up. Presence of antibody at diagnosis was associated with milder symptoms and greater exercise capacity at follow up and persistence of antibody at follow up was associated with stable disease and milder symptoms at diagnosis. CONCLUSIONS: Cardiac specific autoantibodies in dilated cardiomyopathy become undetectable with disease progression; this is a recognised feature of other autoimmune conditions, such as type 1 diabetes. Detection of these antibodies at diagnosis and at follow up may provide a non-invasive marker of early dilated cardiomyopathy.